2012
DOI: 10.12816/0003143
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and Antioxidant Enzymes in Venous and Cord Blood of Late Preterm and Term Omani Mothers

Abstract: This study assessed the role of oxidative stress in parturition in Omani mothers following growing reports that late preterm neonates were at greater risk than term neonates of perinatal death. Methods: Venous blood samples were collected during labour, and cord (neonatal) blood samples were taken after childbirth in late preterm and term from women at Sultan Qaboos University Hospital, Oman. Plasma nitric oxide (NO) concentrations, erythrocyte catalase (CAT). Erythrocyte glutathione peroxidase (GPx) activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In one study that we reviewed, researchers found alterations in metabolite levels of NO synthesis in maternal blood, venous cord blood, and arterial cord blood at birth in PTB versus TB (Alexandre-Gouabau et al, 2013). In another study, investigators found NO levels measured in maternal blood during labor to be higher in mothers delivering late preterm infants (34-37 weeks of GA) compared to TB (>37 weeks of GA; Abiaka & Machado, 2012). However, they found no differences in the cord blood of PTB compared to TB, suggesting a potential role of dysregulated maternal RNS in the mechanism of late PTB.…”
Section: Rns and Sources Of Rnsmentioning
confidence: 96%
See 2 more Smart Citations
“…In one study that we reviewed, researchers found alterations in metabolite levels of NO synthesis in maternal blood, venous cord blood, and arterial cord blood at birth in PTB versus TB (Alexandre-Gouabau et al, 2013). In another study, investigators found NO levels measured in maternal blood during labor to be higher in mothers delivering late preterm infants (34-37 weeks of GA) compared to TB (>37 weeks of GA; Abiaka & Machado, 2012). However, they found no differences in the cord blood of PTB compared to TB, suggesting a potential role of dysregulated maternal RNS in the mechanism of late PTB.…”
Section: Rns and Sources Of Rnsmentioning
confidence: 96%
“…It is a tetrameric ferriheme that decomposes H 2 O 2 to form H 2 O and O 2 (Kodydková, Vávrová, Kocík, & Ž ák, 2014;Pisoschi & Pop, 2015). In the studies we reviewed, researchers found no differences in CAT levels in maternal or cord blood specimens (Abiaka & Machado, 2012;Lázár, Orvos, Sz} oll} osi, & Varga, 2015;Soydinç et al, 2012Soydinç et al, , 2013 and no changes in CAT protein expression in the myometrium tissue (Khan, Matharoo-Ball, & Shaw, 2010) between PTB and TB. However, Soydinc et al (2013) did find lower CAT levels in the vaginal wash fluid in pPROM compared to a matched control group.…”
Section: Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these oxidative stress markers have been shown to negatively correlate with birth weight and gestational age of the newborn14. Preterm mothers and neonates also have elevated levels of plasma nitric oxide and lipid peroxidation and decreased glutathione and glutathione peroxidase activity15161736. Antioxidants have been shown to reduce oxidative stress and inflammatory markers in both human gestational tissues and experimental models of PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm neonates and mothers have elevated levels of markers of oxidative stress, which negatively correlate with birthweight and gestational age at birth121314151617. Elevated levels of markers of oxidative stress have been detected in preterm infants beyond their first 100 days of life18, suggesting that oxidative stress established prenatally may persist throughout infancy.…”
mentioning
confidence: 99%